Odpowiedzi

2009-12-09T20:22:29+01:00
(x+4)²-(x+8)(x-8)=96
x²+8x+16-(x²-64)=96
x²+8x+16-x²+64=96
8x=96-72
8x=24 / :8
x=3

-(x-0,4)(x+0,4)+(x-0,4)²=-0,08
-(x²-0,16)+x²-0,8x+0,16=-0,08
-x²+0,16+x²-0,8x+0,16=-0,08
-0,08x=-0,08-0,016-0,016
-0,08x=-0,112 /:(-0,08)
x=1,4

3(x+2)²+(2x-1)²-7(x+3)(x-3)=28
3(x²+4x+4)+4x²-4x+1-7(x²-9)=28
3x²+12x+12+4x²-4x+1-7x²+63=28
3x²+4x²-7x²-12x-4x=28-12-1-63
-16x=-48 /:(-16)
x=3

5(x+3)²-5(x-4)(x+4)+12=77
5(x²+6x+9)-5(x²-16)+12=77
5x²+30x+45-5x²+80+12=77
30x=77-12-80-30
30x=-45
x=-1,5


(2y-1)(2y+1)-(2y-3)²+12y=38
4y²-1-4y²-12y+9+12y=38
0≠28 <- sprzeczne
Najlepsza Odpowiedź!
2009-12-09T20:25:29+01:00
A) (x+4)²-(x+8)(x-8)=96
8x+16+x²-x²+64=96
8x+80=96 |-70
8x=16
x=2
spr. 8x+80=96
16+80=96
96=96
b)-(x-0,4)(x+0,4)+(x-0,4)²=-0,08
-(x²-0,16)+x²-0,8x+0,16=-0,08
-x²+0,16+x²-0,8x+0,16=-0,08
0,32-0,8x=-0,08 |-0,32
-0,4=-0,8x
x=0,5

spr.0,32-0,8x=-0,08
0,32-0,4=-0,08

c)3(x+2)²+(2x-1)²-7(x+3)(x-3)=28
3(x²+4x+4)+4x²+1-4x-7(x²-9)=28
3x²+12x+12+4x²+1-4x-7x²+63=28
8x+64=28 |-64
8x=-36
x=-4,5

spr. 8x+64=28
-36+64=28
28=28


d)5(x+3)²-5(x-4)(x+4)+12=77
5(x²+6x+9)-5(x²+16)+12=77
5x²+30x+45-5x²-80+12=77
30x-23=77 |+23
30x=100
x=10/3

spr.
30x-23=77
300/3-23=77
100-23=77
77=77

e)(2y-1)(2y+1)-(2y-3)²+12y=38
4y²-1-(4y²-12y+9)+12y=38
4y²-1-4y²+12y-9+12y=38
-10+24y=38 |+10
24y=48
y=2

-10+24y=38
-10+48=38
38=38